The Assault on School Teacher Bargaining in Ontario - Rose, Joseph (Relations industrielles / Industrial Relations, 2002)
SummaryBetween 1975 and 1997, school teacher bargaining was conducted under the School Boards and Teachers Collective Negotiations Act (Bill 100). By most accounts, the teacher bargaining law was successful in promoting bilateral settlements with minimal strike activity. Following its election in 1995, the Harris government reduced public expenditures and introduced educational reforms. In doing so, it repealed Bill 100 and passed laws restricting teacher bargaining. These measures ranged from imposing restrictions on the scope of negotiable issues to attempts to make “voluntary” extracurricular activities mandatory. This study finds that the government’s blunt and heavy-handed efforts to control collective bargaining processes and outcomes, not only proved futile, but led to an increase in work stoppages and protracted guerilla warfare at the school board level.